KONSEP URGENSI PENDIDIKAN ISLAM MULTIKULTURAL DAN PERMASALAHANNYA - Eko Setiawan (Edudeena : Journal of Islamic Religious Education, 2019)
Abstract: Basically Multicultural Islamic education is an education whose founding and organizing is inspired by the spirit of multiculturalism, in order to realize a harmonious life. Specifically, multicultural education of Islam is an education based on the joints of Islam who want to explore differences as a necessity. The multicultural education model is an offer of an educational model that carries an ideology that understands, respects, and values the dignity of human beings wherever they are and wherever they come from. Multicultural Islamic education is an inherent desire of all humankind, because it is in need of education model of this multicultural education as a development process that does not recognize the difference of the difference in human interaction. Education that values heterogeneity and plurality, an education that values cultural values, ethnicity, tribe, and religion. Abstrak: Pada dasarnya pendidikan Islam Multikultural adalah pendidikan yang pendirian dan penyelenggaraanya diilhami oleh semangat multikulturalisme, agar terwujud kehidupan yang harmonis. Secara spesifik, pendidikan Islam multikultural adalah pendidikan yang berlandaskan sendi-sendi Islam yang ingin mengeksplorasi perbedaan sebagai sebuah keniscayaan. Model pendidikan multikultural merupakan sebuah tawaran model pendidikan yang mengusung ideologi yang memahami, menghormati, dan menghargai harkat martabat manusia di manapun dia berada dan dari manapun asalnya. Pendidikan Islam multikultural secara inhern merupakan dambaan semua umat manusia, karena sangat membutuhkan pendidikan model pendidikan multikultural ini sebagai proses pengembangan yang tidak mengenal sekat perbedaan dalam interaksi manusia. Pendidikan yang menghargai heterogenitas dan pluralitas, pendidikan yang menjunjung tinggi nilai kebudayaan, etnis, suku, dan agama.